Awareness of black garlic benefits to health: A preliminary study / Neni Kartini Che Mohd Ramli, Suriyati Ujang and Nazirah Ramli - Che Mohd Ramli, Neni Kartini; Ujang, Suriyati; Ramli, Nazirah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Black garlic is a beneficial and usable food product resulting from fresh garlic fermentation. It is used in Asian cuisine and is made by heating the whole bulb of garlic at a temperature of 60 - 90oC and humidity of 70 - 90% over a period of several weeks. In Korea, black garlic is added to energy drinks as a health product and in Thailand it is claimed to increase human longevity. Black garlic has many health benefits such as able to reduce homocysteine levels in the bloodstream, improves blood circulation by boosting hydrogen sulphide production that can maintain stable blood pressure levels and support normal clotting. It can stimulate the activity of white blood cells in the immune system to fight infections. It is believed to be beneficial in normalizing blood sugar levels by enhancing insulin production. Black garlic can also increase the level of testosterone in both men and women indicating that it may be beneficial in boosting libido. Not much is known about the level of awareness in Malaysia concerning the health benefits of black garlic. Thus, this study was carried out to evaluate awareness regarding the health benefits of black garlic among academic staff in a higher learning institution in the East Coast of Malaysia. A questionnaire was constructed and then distributed via google form, and the data were analyzed using SPSS. The results showed that nearly three quarters of the respondents were aware of the black garlic's health benefits, but only a few consumed it.